A Syringe‐Based DNAzyme Sensor for Bacterial Detection. Issue 2 (7th April 2021) - Esmaeili Samani, Sahar; McConnell, Erin M.; Chang, Dingran; Rothenbroker, Meghan; Filipe, Carlos D. M.; Li, Yingfu
Abstract: We present a simple approach for bacterial detection that uses a bead‐bound RNA‐cleaving DNAzyme (RcD) and a syringe. The RcD used in this study, F‐EC1, is fluorescently labelled and can be specifically activated by a protein target released specifically by E. coli . Upon immobilization on agarose beads, the kinetic behaviour of F‐EC1 remains similar to that in solution. The F‐EC1‐agarose system was able to detect as few as 1, 000 CFUs of E. coli and retained high recognition specificity. A syringe‐based biosensor was subsequently designed, where F‐EC1‐bearing agarose beads were loaded onto a filter‐containing column. Upon incubation with an E. coli containing reaction mixture, the cleavage fragment released from the beads was filtered onto a nitrocellulose paper to be detected. The sensor was used to achieve the detection of E. coli in water, milk, and apple juice. This method is cost‐effective, simple to use, and can be adapted to other ligand‐responsive RNA‐cleaving DNAzymes. Abstract : Bacterial detection with a syringe : The use of a syringe and agarose beads immobilized with a bacteria‐specific RNA‐cleaving DNAzyme (RCD) offers a simple way to carry out detection of a specific bacterium from complex sample matrices.